Annual Plan 1971-72 Government of the Union Territory of Goa, Daman and Diu - Planning Commission (Planning Commission, 1971)
The year 1971-72 is the third year of the b-the Five Year Plan 1969-7b-. -All the schemes included in the b-the Plan are in the process of implementation. In 1969-70 Rs.571.lb-8 lakhs were spent against the outlay of Rs. 668.8b- lakh. In the last year the expenditure on plan schemes increased to Rs.670.305' lakhs against the outlay of Re.7b-2.b-2 lakhs. Rs.810.00 lakhs have been allocated for the 3rd Year i.e. 1971-72 and concerted efforts are being made since the beginning of the year to achieve the targets fixed for the year.
Planning Department
Government of The Union Territory of Goa, Daman and Diu Planning Department